2001
DOI: 10.1046/j.1365-2559.2001.01309.x
|View full text |Cite
|
Sign up to set email alerts
|

CD99/MIC‐2 surface protein expression in breast carcinomas

Abstract: CD99/MIC-2 is expressed in breast carcinomas, especially in the matrix-producing variant of metaplastic carcinomas, which impairs its use as a marker to differentiate metaplastic carcinomas from primary and metastatic sarcomas of the breast. It seems to have no prognostic implications. However, phenotype similarities with other chondromyxoid tumours that also express the protein, like mesenchymal chondrosarcomas, suggest a relationship between MIC-2 reactivity and morphological differentiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 15 publications
1
42
1
Order By: Relevance
“…16,17 Such findings supported that matrix-producing carcinoma of the breast was associated with myoepithelial cell-like differentiation: although the metaplastic cells of matrixproducing carcinoma have myoepithelial cell-like features, the origin of this cancer is considered to be derived from mammary epithelial cells. A recent report showed that CD99 (MIC2) was expressed in breast carcinoma, especially in matrix-producing carcinoma, but concluded that there was no significance between CD99 (MIC2) expression and the proliferating rate or nodal status; 18 however, it was suggested that CD99 (MIC2) expression was a useful marker to differentiate metaplastic carcinomas from primary or metastatic sarcomas of the breast, although its biological significance remains unclear. As three of our cases were positive for CD99 (MIC2), histological and immunohistological findings were compatible with matrix-producing carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Such findings supported that matrix-producing carcinoma of the breast was associated with myoepithelial cell-like differentiation: although the metaplastic cells of matrixproducing carcinoma have myoepithelial cell-like features, the origin of this cancer is considered to be derived from mammary epithelial cells. A recent report showed that CD99 (MIC2) was expressed in breast carcinoma, especially in matrix-producing carcinoma, but concluded that there was no significance between CD99 (MIC2) expression and the proliferating rate or nodal status; 18 however, it was suggested that CD99 (MIC2) expression was a useful marker to differentiate metaplastic carcinomas from primary or metastatic sarcomas of the breast, although its biological significance remains unclear. As three of our cases were positive for CD99 (MIC2), histological and immunohistological findings were compatible with matrix-producing carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…CD99 is a transmembrane protein expressed particularly in mature plasma cells, cortical thymocytes, pancreatic islet cells, granulosa cells of the ovary and Sertoli cells of the testis [1,2]. Its expression is strong in the Ewing sarcoma/primitive neuroectodermal tumor (PNET) family [3], but it can also occur in many other mesenchymal [4,5], hematopoietic [6,7] and even some epithelial tumors [2,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Its expression is strong in the Ewing sarcoma/primitive neuroectodermal tumor (PNET) family [3], but it can also occur in many other mesenchymal [4,5], hematopoietic [6,7] and even some epithelial tumors [2,8,9]. CD99 is involved in differentiation of primitive neuroectodermal cells [10] and apoptosis of T cells [11], but its role in epithelial tissues and neoplasms originating from them remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…The positive expression of CD99 (MIC2), a cell surface glycoprotein involved in cell adhesion, plays a crucial role in the diagnosis of ES/PNET (10). However, CD99 may also be expressed in other tumours, including metaplastic carcinoma of the breast, neuroendocrine carcinoma, lymphoma and rhabdomyosarcoma (11). In our patient, small cell carcinoma, neuroendocrine carcinoma and malignant lymphoma were excluded by negative staining for cytokeratins, chromogranin A and LCA.…”
Section: Discussionmentioning
confidence: 67%